STUDI LITERATUR: TANTANGAN DAN SOLUSI PEMBELAJARAN JARAK JAUH PADA PENDIDIKAN DASAR DAN MENENGAH DI INDONESIA (2020–2025) - Kosim, Ahmad; Ermawati, Eny; Sarwiyanti, Sarwiyanti; Wicaksono, Dirgantara (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study aims to comprehensively examine the dynamics of challenges and solutions in the implementation of Distance Learning (DL) at the primary and secondary education levels in Indonesia during the period of 2020–2025. A narrative literature review approach was employed by analyzing 30 credible sources, including reputable national and international journal articles as well as official reports from relevant institutions. The synthesis of the literature reveals that the challenges of distance learning are multidimensional, encompassing limited technological access and infrastructure, insufficient digital pedagogical readiness among educators, declining student motivation and engagement, and disparities in family support, particularly in rural and disadvantaged (3T) areas. The findings also indicate significant learning loss resulting from the low quality of interaction in online learning environments. In response to these challenges, several solutions and best practices were identified, such as strengthening teachers’ digital literacy, implementing microlearning and project-based learning approaches, utilizing low-cost interactive media, and enhancing collaboration between schools and families. The study concludes that the effectiveness of distance learning is highly dependent on synergy among policy frameworks, teacher readiness, infrastructure support, and students’ learning environments. These findings are expected to serve as a foundation for the development of more inclusive, adaptive, and equitable digital education policies in the future. ABSTRAK Penelitian ini bertujuan untuk mengkaji secara komprehensif dinamika tantangan dan solusi dalam implementasi Pembelajaran Jarak Jauh (PJJ) pada jenjang pendidikan dasar dan menengah di Indonesia selama periode 2020–2025. Penelitian menggunakan pendekatan studi literatur naratif dengan menganalisis 30 sumber kredibel yang terdiri atas artikel jurnal nasional dan internasional bereputasi serta laporan resmi lembaga terkait. Hasil sintesis menunjukkan bahwa tantangan PJJ bersifat multidimensional, mencakup keterbatasan akses dan infrastruktur teknologi, ketidaksiapan pedagogis digital pendidik, penurunan motivasi dan keterlibatan siswa, serta ketimpangan dukungan keluarga, khususnya pada wilayah pedesaan dan daerah 3T. Temuan juga mengungkap adanya indikasi learning loss yang signifikan akibat rendahnya kualitas interaksi pembelajaran daring. Sebagai respons terhadap tantangan tersebut, berbagai solusi dan praktik baik diidentifikasi, antara lain penguatan literasi digital guru, penerapan microlearning dan pembelajaran berbasis proyek, pemanfaatan media interaktif berbiaya rendah, serta penguatan kolaborasi antara sekolah dan keluarga. Penelitian ini menyimpulkan bahwa efektivitas PJJ sangat bergantung pada sinergi antara kebijakan, kesiapan pendidik, dukungan infrastruktur, dan lingkungan belajar siswa. Hasil kajian ini diharapkan dapat menjadi dasar perumusan kebijakan pendidikan digital yang lebih inklusif, adaptif, dan berkeadilan di masa depan.